PROJECT-BASED LEARNING TO ENHANCE ECONOMIC LITERACY - Yuliani; Sugiono; Forijati (Count : Journal of Accounting, Business and Management, 2025)
This study investigates the effectiveness of the Project-Based Learning (PBL) model in enhancing students’ economic literacy at MAN 1 Kediri City. The research was motivated by the low level of economic literacy among students, which is attributed to the dominance of conventional, theory-based instructional approaches that limit student engagement and practical understanding. To address this issue, a Classroom Action Research (CAR) design was employed across two cycles, each consisting of four stages: planning, implementation, observation, and reflection. A total of 28 students from grade X-F participated in the study. Data collection techniques included pre-tests and post-tests to measure economic literacy gains, observation sheets to assess engagement, interviews to gather student perceptions, and documentation of project outputs. In Cycle 1, the average student score increased by 13% compared to the pre-test, although not all students achieved classical completeness. After revising the instructional strategy, Cycle 2 yielded a further 20% increase in scores, with all students meeting or exceeding the minimum mastery criteria. Qualitative data also indicated improved motivation, collaboration, and critical thinking. The study findings are consistent with prior literature, confirming that PBL enhances not only conceptual understanding but also student engagement and higher-order thinking skills. This research contributes novel insights by applying a two-cycle CAR framework within an Islamic high school context, integrating both quantitative and qualitative analysis. The results suggest that PBL is a highly effective pedagogical strategy for improving economic literacy and can be adapted in broader educational settings to support meaningful, student-centered learning.